The existence of behavioral biases and personality traits in explaining the effect of fundamental and technical analysis to investment performance in Indonesia stock exchange / Ika Yanuarti Loebiantoro, H.C. Eaw and Nursyamilah Annuar - Loebiantoro, Ika Yanuarti; Eaw, H.C; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2021)
Rational investors focus on the fundamental and technical analysis in their investment decisions. In fundamental analysis, they consider economic conditions, industry analysis, and company analysis if they use a top-down approach, and vice versa if they use a bottom-up approach. Technical analysis focuses on the historical movement of stock price to predict the future price by using the pattern of a chart. However, in modern finance, investors are not fully rational as they are also affected by the psychological factors when making their investment decisions. These psychological factors then create behavioral biases, which becomes the basic assumption of behavioral finance This research is aimed at investigating the role of availability bias and disposition effect as behavioral biases that make investors irrational in their behaviors and whether it is supported by the Big Five Personality Traits, which include openness, conscientiousness, extraversion, agreeableness, and neuroticism (OCEAN). It needs to explore the influence of fundamental analysis and technical analysis on investment performance with the existence of behavioral biases as mediating variable and personality traits as a moderating variable between fundamental analysis and behavioral biases.